Reactive Oxygen Species in Pathogenesis of Atherosclerosis - V. Goncharov, Nikolay; V. Avdonin, Pavel; D. Nadeev, Alexander; L. Zharkikh, Irina; O. Jenkins, Richard (Current Pharmaceutical Design, 2015)
The volume of publications on the role of reactive oxygen species (ROS) in biological processes has been increasing exponentially over the last decades. ROS in large amounts clearly have detrimental effects on cell physiology, whereas low concentrations of ROS are permanently produced in cells and play a role as signaling molecules. An imbalance in ROS production and defense mechanisms can lead to pathological vascular remodeling, atherosclerosis being among them. The aim of this review is to examine different sources of ROS from the point of view of their participation in pathogenesis of atherosclerosis and related cardiovascular risk. Among the possible sources of ROS discussed here are mitochondria, NADPH-oxidases, xanthine oxidase, peroxidases, NO-synthases, cytochrome P450, cyclooxygenases, lipoxygenases, and hemoglobin of red blood cells. A great challenge for future research is to establish interrelations, feedback and feed-forward regulation mechanisms of various sources of ROS in development of atherosclerosis and other vascular pathologies.
Keywords: NADPH-oxidase